The Role of Substance P in the Regulation of Bone and Cartilage Metabolic Activity - Li, Fu-Xing-Zi; Xu, Feng; Lin, Xiao; Wu, Feng; Zhong, Jia-Yu; Wang, Yi; Guo, Bei; Zheng, Ming-Hui; Shan, Su-Kang; Yuan, Ling-Qing (Frontiers in Endocrinology, 2020)
Substance P (SP) is a neuropeptide that is released from sensory nerve endings and is widely present in nerve fibres. It acts on bones and related tissues by binding to receptors, thereby regulating bone metabolism, cartilage metabolism and fracture healing. SP has attracted widespread attention as a signalling substance that can be recognized by both the immune system and the nervous system. Previous studies have shown that bone and chondrocytes can synthesize and secrete sensory neuropeptides and express their receptors, and can promote proliferation, differentiation, apoptosis, matrix synthesis and the degradation of target cells through autocrine/paracrine modes. In this paper, we review the research progress made in this field in recent years in order to provide a reference for further understanding the regulatory mechanism of bone and cartilage physiology and pathological metabolism.